The Influence of Sales Turnover, Determination of Sales Sales Costs and Customer Payment Systems on Company Profits at PT. King Asia Food Malang - Isa Kholili (CV. AFDIFAL MAJU BERKAH, 2022)
The development of the business world in Indonesia, which is increasingly competitive, requires every company to be able to manage company management to be more professional. The purpose of this study was to determine the effect of sales turnover, sales costing, and customer payment systems partially and simultaneously on company profits at PT. King Asia Food. The sampling technique used in this study is a saturated sampling technique, all members of the population are used as samples. There are 30 respondents consisting of 20 sales people and 10 people in the office staff. This study uses a quantitative descriptive method while data processing uses the SPSS version 23 program. The results showed that the sales turnover variable and sales sales costing did not partially affect the company's profits, thus H0 was accepted and Ha was rejected, while for the customer payment system it partially affected the company's profits, thus H0 was rejected and Ha was accepted, will but the three variables simultaneously affect the company's profits, thus H0 is rejected and Ha is accepted.